Single‐cell sequencing reveals the role of IL‐33+ endothelial subsets in promoting early gastric cancer progression - Li Zhou; Mei Yang; Chao Deng; Manqiu Hu; Suhua Wu; Kewen Lai; Lili Zhang; Zhiji Chen; Qin Tang; Qingliang Wang; Lu Chen; Runmin Zha; et al. (iMeta)
Abstract Early gastric cancer (EGC) represents a critical stage in preventing and controlling the progression from gastritis to advanced gastric cancer (AGC). Therefore, identifying the single‐cell characteristics of EGC, particularly the cellular composition of the tumor microenvironment (TME), as well as identifying potential predictive markers and therapeutic targets, could significantly enhance the monitoring of gastric cancer and improve clinical cure rates. We constructed a comprehensive single‐cell RNA sequencing atlas for 184,426 high‐quality gastric cancer cells from various stages, utilizing clinical biopsies and surgical samples. Our single‐cell atlas highlights the cellular and molecular characteristics of EGC. Eight distinct cell lineage states were identified, and it was observed that the number of epithelial cell meta‐clusters gradually decreased, while the number of T&NK, B, plasma, fibroblast, myeloid, and endothelial cells increased with disease progression. Certain epithelial subclusters (metaplastic stem‐like cells (MSCs), pit mucous‐like cells (PMC‐like), proliferating cells), T‐cell subclusters (Treg, CCR7+ naive, CH25H+ CD4+, TEM CD8+, and GFPT2+ CD8+ T cells), and endothelial subclusters (IL‐33+ Venous‐1 and AMAMTSL2+ Artery‐2) were found to be increased in EGC. The Venous‐1 subcluster was found to express high levels of IL‐33. Mechanistically, it was revealed that IL‐33 enhances the survival and angiogenesis of endothelial cells by upregulating the expression of adhesion proteins CD34 and PECAM1. Patient‐derived EGC and AGC organoids were subsequently generated, and it was demonstrated that endothelial‐derived IL‐33 promoted the growth of both EGC and AGC organoids ex vitro and in vivo. Furthermore, IL‐33 was found to increase the expression of KRT17 in EGC organoids. Notably, we also found that high expression of IL‐33 was positively correlated with the depth of invasion and malignancy of EGC. This study provides novel insights into the single‐cell components involved in EGC and reveals the role of the IL‐33+ endothelial subcluster in EGC progression.